2022
DOI: 10.1080/20002297.2022.2105022
|View full text |Cite
|
Sign up to set email alerts
|

Application of fluoride disturbs plaque microecology and promotes remineralization of enamel initial caries

Abstract: Background The caries-preventive effect of topical fluoride application has been corroborated by a number of clinical studies. However, the effect of fluoride on oral microecology remains unclear. Objective To monitor the effect of fluoride on dental plaque microecology and demineralization/remineralization balance of enamel initial caries. Methods Three-year-old children were enrolled and treated with fluoride at baseline and 6 months. Inter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 59 publications
0
4
0
Order By: Relevance
“…GI, BI, and PLI are all important indicators for evaluating periodontal health [29,30] . Previous clinical studies have mainly focused on the effectiveness of PMC in the restoration of dental caries in children.…”
Section: The Impact Of Metal Prefabricated Crowns and All Ceramic Cro...mentioning
confidence: 99%
“…GI, BI, and PLI are all important indicators for evaluating periodontal health [29,30] . Previous clinical studies have mainly focused on the effectiveness of PMC in the restoration of dental caries in children.…”
Section: The Impact Of Metal Prefabricated Crowns and All Ceramic Cro...mentioning
confidence: 99%
“…Appropriate F intake or topical application is one of the most effective methods to prevent dental caries because uorapatite formed by F-doping in hydroxyapatite strengthens the crystal stability and thus improves caries resistance. 5,6 At present, the most commonly used drugs for professional uoride treatments are NaF, SnF 2 , and APF. 47 Therefore, 6 healthy premolars were selected to evaluate the capability of these three anti-caries drugs by analyzing the absorption of F in the teeth.…”
Section: Evaluation Of F Absorption From Anticaries Drugsmentioning
confidence: 99%
“…4 A considerable amount of literature has suggested that appropriate uoride intake or topical uoride application prevents and treats dental caries by disturbing plaque microecology, reducing enamel solubility, and promoting enamel remineralization, which is benecial to dental health. 5,6 Elucidating the role of F in preventing dental caries has been a crucial research topic in the dental eld over the past few decades. 7,8 Although considerable progress has been achieved, the scarcity of technology to visualize F in teeth still hampers dentists from obtaining a comprehensive understanding of the role of anti-caries uorides.…”
Section: Introductionmentioning
confidence: 99%
“…Constant exposure to acidic conditions leads to the demineralization of tooth enamel (Marsh & Nyvad, 2008; Takahashi & Nyvad, 2011). This effect can be partially reversed by using fluoride, which alters the dental plaque microenvironment and promotes remineralization of the enamel (Zhang et al, 2022). Host variables, encompassing various demographic, socioeconomic, and behavioral factors, also influence the development of caries (Arora et al, 2011; Imes et al, 2021; Pierce et al, 2019).…”
Section: Introductionmentioning
confidence: 99%